Estrategias didácticas constructivistas para el logro de resultados de aprendizaje en Biología. Año lectivo 2022-2023 - Cango Sánchez, Natalia Germania (2023)
The aim of the research pretends to strengthen the achievement of learning outcomes in the students through the application of constructivist didactic strategies, that allow to improve the teaching and learning process of Biology of first year of baccalaureate of the educative unit “La Dolorosa” academic period 2022 – 20023. For the research process it was considered the inductive method, since the identification of the problem, it was proposed the information search to provide solution alternatives. It refers to qualitative approach, because it allowed to determine relevant characteristics of the educative reality regarding to the application of constructivist didactic strategies for the learning performance in students. On the other hand, regarding the nature of the information, it belongs to a participative action research, so that, since the problem detection, it was proposed to potentiate the learning results through the intervention proposal, in which there were planned and applied seven lesson plans. Moreover, the research design is transversal, because it was made in a very short period of time and finally for the data collection, evaluation instruments and investigation were used. The obtained results in this research show that the seeking strategy, organization and information selection, collaborative work strategy, the learning strategy by discovering, the explanatory – illustrative strategy, and experimentation strategy, are effective for the topics of teaching such as: organic biomolecules, and metabolism, in Biology. It was concluded that these strategies are effective as long as they are organized depending on the topics with the respective techniques, physical and technological resources and its didactic material. Keywords: constructivist didactic strategies, achievement of learning outcomes, teaching and learning process, learning consolidation.